PENINGKATAN KEMAMPUAN KOGNITIF MELALUI PERMAINAN MENCARI URUTAN LAMBANG BILANGAN PADA ANAK USIA 5-6 TAHUN - (F54210041), Nurmalasari; ., Marmawi; ., Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
This research is a form of action research with descriptive methods . Subjects were 1 teacher and children , amounting to 15 children . Based on the research that has been done and through the results obtained after an analysis of data that : 1 ) Planning for meningatkan learning cognitive skills through the game looking for a symbol sequence numbers 1-10 in children can be categorized as